1979
DOI: 10.1002/app.1979.070230319
|View full text |Cite
|
Sign up to set email alerts
|

The origin of residual internal stress in solvent‐cast thermoplastic coatings

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(141 citation statements)
references
References 4 publications
7
133
0
1
Order By: Relevance
“…In this regard, it has been observed that the coatings do not exhibit cracking below a certain critical thickness ranging from 0.5 to 1¯m. 53) The analysis of the cracking evolution of the deposited films (see Fig. 7) shows that not only the amount of deposited ceramic (see Fig.…”
Section: ¹1mentioning
confidence: 99%
“…In this regard, it has been observed that the coatings do not exhibit cracking below a certain critical thickness ranging from 0.5 to 1¯m. 53) The analysis of the cracking evolution of the deposited films (see Fig. 7) shows that not only the amount of deposited ceramic (see Fig.…”
Section: ¹1mentioning
confidence: 99%
“…The Poisson's ratio of the HPMC films was taken as 0.35, which is a common approximation value for many polymeric materials (4,14,15). Due to the difficulties of the determination of the fraction of moisture at solidification point, in this study a value of 0.12 was taken, while Croll (1979) suggested a value of 0.162 for polyisobutyl methacrylate.…”
Section: Loss Of Stressmentioning
confidence: 99%
“…Due to the difficulties of the determination of the fraction of moisture at solidification point, in this study a value of 0.12 was taken, while Croll (1979) suggested a value of 0.162 for polyisobutyl methacrylate. Despite this arbitrariness, the trend of the correlation between the excess of internal stress and the moisture content remains the same and the estimated internal stresses are in the same order of magnitude as the values reported by others (7).…”
Section: Loss Of Stressmentioning
confidence: 99%
“…Internal stresses arise due to shrinkage of the film upon solvent evaporation, thermal stress due to the difference in thermal expansion of the substrate and film, and volumetric stress as the substrate swells during storage. Equation 4 can be used to estimate total internal stress (P) within a film coating, [41][42][43][44] where E is the elastic modulus of the film, ν is Poisson's ratio, Φ s is the volume fraction of solvent at the solidification point of the film, Φ r is the volume fraction of solvent in an air dried film, Δα cubic is the difference in coefficient of thermal expansion between the film and substrate, ΔT is the difference between the Tg of the film and the temperature during manufacturing and storage, ΔV is the volumetric change of the substrate, and V is the original volume of the substrate core.…”
Section: Polymer Adhesionmentioning
confidence: 99%